Immune and inflammatory response in atopic elite endurance athletes - Teixeira, R. N.; dos Santos Leite, G.; Gorjao, R.; Palmeira, P.; Santos, C. M. M.; Zambonatto, R.; de Oliveira, H. H.; Levada, A. C.; Fiks, I. N.; Carvalho, C. R. F. (International Journal of Sports Medicine, 2018)
The present study aimed to compare the immune and inflammatory responses between atopic (n=20) and non-atopic (n=39) elite endurance athletes. Fifty-nine elite runners and triathletes were assessed for the following measurements: Th1, Th2 and lymphocyte phenotyping and plasma levels of cortisol, chemokines, inflammatory cytokines and specific immunoglobulin E (IgE). Levels of salivary IgA, allergic symptoms and training data were also evaluated. No difference was observed in baseline lymphocyte levels. However, the Th1 lymphocytes of atopic athletes presented a lower response after activation. In contrast to this result, levels of salivary IgA and CXCL9 chemokine were higher in the atopic athletes. It was observed that the volume of training per week was linearly associated with Th1 levels, allergic symptoms and IgE levels. In addition, linear multiple regression analysis demonstrated that the volume of training was the only factor associated with allergic symptoms in atopic athletes (r=0.53; p=0.04). These results suggest that compared to non-atopic athletes, atopic athletes present a reduced Th1 response and higher levels of salivary IgA. Training volume is associated with the immune response and allergic symptoms, which suggests that they may play a role in the atopy in elite endurance athletes.